Preliminary Study of Biological Traces on the Crime Scene - MARATKYZY, Ainur; DILBARKHANOVA, Zhanat R. (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
The article discusses the features of detection, fixation and withdrawal of traces of biological origin for forensic and expert research. Currently, evidences of biological origin derived from various life processes of various biological objects become increasingly important for crime investigation. Biological traces have been studied and categorized by various scientists, however, with the technological progress in general and the development of the forensic technology in particular, an opportunity arises to study unconventional biological traces previously neglected by criminologists and experts, apart from the more accurate study of traditional biological traces, such as blood, semen, and saliva. Such studies provide an opportunity to more effectively study crimes, and to convict the guilty. Therefore, the issue raised in the framework of this article is very timely and relevant. The author reveals the features of investigative actions, in particular, inspection of the crime scene, fixation, withdrawal, transportation, and storage of various traces of biological origin. It has been shown that taking these characteristics into account may provide successful investigation, while ignoring them may not only complicate the case, but also cause errors in the investigation, which, in turn, may have negative effect on court judgment, and result in conviction of an innocent person